Colonization, resistance to bile, and virulence properties of Escherichia coli strains: Unusual characteristics associated with biliary tract diseases. (October 2017) - Razaghi, Maryam; Tajeddin, Elahe; Ganji, Leila; Alebouyeh, Masoud; Alizadeh, Amir Houshang Mohammad; Sadeghi, Amir; Zali, Mohammad Reza
Abstract: Escherichia coli is the species that is most frequently isolated from bile of patients with biliary tract diseases. This study was aimed to investigate any association between resistance and virulence properties of these isolates with occurrence of the diseases. A total of 102 bile samples were obtained from patients subjected to endoscopic retrograde cholangiopancreatography for different biliary diseases. Clinical data were collected and culture of the bile samples was done on selective media. Resistance of characterized Escherichia coli isolates to deoxycholate sodium (0–7%) and nineteen antibiotics was determined and PCR using 16 pairs of primers targeting stx1, stx2, exhA, eae, bfp, agg, pcvd432, lt, st, ipaH, pic, pet, ast, set, sen, and cdtB genes was done. Our results showed a statistically significant association between E. coli colonization and existence of common bile duct and gallbladder stones ( p value 0.028). Out of the 22 E. coli strains (22/102) multidrug resistance phenotype was present in 95.45%. None of the strains belonged to common E. coli pathotypes. However, bfp + EhxA-hly, bfp + astA, bfp + EhxA - hly + pic, and EhxA-hly + pic + astA, bfp, and astA genotypes were detected in these strains. bfp (7/22, 31.8%) and astA (5/22, 22.7%) were among most frequent virulence factors in these strains. Results of this study showed significant association between colonization of E. coli and choledocholithiasis. Unusual existence of virulence gene combinations in these strains and their resistance to DOC and multiple classes of antibiotics could be considered as possible causes of their persistence in this harsh microenvironment. Highlights: Colonization of E. coli could be mediated by Bfp in bile duct. Enterotoxin related genes were most frequent virulence factors detected in these strains in patients with CBD stone. Ability of these strains to resist bile components suggests their adaptation for colonization and growth in harsh niche of the biliary tract.